Wellness Programs and Means of Getting Employees to Stay Healthy: A Response to Kristin Van Busum and Soeren Mattke - Bahaudin G. Mujtaba; Frank J. Cavico (Kerman University of Medical Sciences, 2014)
This is a short writing in response to the "Financial Incentives: Only One Piece of the Workplace Wellness Puzzle" (1) by Kristin Van Busum and Soeren Mattke of the RAND Health Advisory Services, RAND Corporation, in Boston.